Changes in chemical and microbiological quality of semi-processed black soldier fly (Hermetia illucens L.) larval meal during storage - Kamau, E.; Mutungi, C.; Kinyuru, J.; Imathiu, S.; Affognon, Hippolyte D.; Ekesi, S.; Nakimbugwe, D.; Fiaboe, K. (Brill, 2020)
Edible insects are receiving attention as a protein source in the food and feed sector. However, successful commercialisation requires mass production matched with appropriate processing and storage techniques. The quality of dried and pulverised black soldier fly larvae stored in woven polypropylene (PP) sacks, polyethylene (PE) bags and plastic containers with screw lid (PL) in ambient and refrigerated environments was monitored over six months. Chemical indicators (oxidation, fatty acid profile), microbiological parameters (total viable counts, yeast and moulds, Enterobacteriaceae, presumptive coliforms, Salmonella) and colour change were examined. Temperature and relative humidity of the storage environments were monitored. In the ambient environment (temperature: 23.6±2.7 °C; relative humidity: 57.6±7.0%), chemical deterioration progressed 1.5 and 1.2 times faster in PP and PE, respectively, compared to PL. Refrigeration (temperature: 5.4±1.1 °C; relative humidity: 97±5.7%) exacerbated spoilage in the PP due to permeation of moisture through the woven strands, but slowed chemical deterioration by factors of 3.3 (PL) and 2.8 (PE). Likewise, based on the average counts of Enterobacteriaceae and yeast and moulds, microbiological deterioration progressed 2.1 and 1.4 times faster in the PP and PE, respectively, while refrigeration retarded build-up of microbial loads by factors of 1.3-9.6. The presence of Salmonella spp. in the experimental product indicates that due attention must be given to adequacy of processing and handling procedures for dried black soldier fly meal.